Research on PIVAS risk assessment and control strategy based on quality risk management (QRM) - Qining Qiu; Guohong Zhu; Gang Peng; Zhenhui Chen; Zhenmao Zhu; Yan Zhou; Yanrong Ye; Yun Shen; Lumin Wang (Elsevier, 2024)
Objective: This study aims to evaluate the effectiveness of the Quality Risk Management (QRM) system in hospital pharmacy intravenous admixture services (PIVAS). Methods: Failure Modes and Effects Analysis (FMEA) and risk matrix methods were used to systematically assess the critical risk points in PIVAS. By collecting and comparing relevant data from 2019 to 2023, key performance indicators (KPIs) before and after the implementation of the QRM system were quantitatively evaluated. Results: The results showed that the safety and efficiency of pharmacy services significantly improved after the implementation of the QRM system. The medication error rate significantly decreased from 3.2% to 1.1%, the average medication preparation time reduced from 15.5 min to 8.2 min, and staff satisfaction increased from 6.0 to 8.5 points. Other indicators, such as cross-contamination rates and handling errors, also showed significant improvement (all outcomes p < 0.001). Discussion: Systematic risk management effectively enhanced the operational performance of PIVAS, reduced medication errors, and improved the quality of healthcare services. This study highlights the key role of QRM in enhancing medication safety and productivity, providing empirical support for the implementation of similar systems in other healthcare institutions.